Підвищення довговічності ґрунтообробних робочих органів - Дудніков, А. А.; Дудніков, І. А.; Дудник, В. В.; Горбенко, О. В.; Лапеннко, Т. Г.; Дудников, А. А.; Дудников, И. А.; Горбенко, А. В.; Dudnikov, A.; Dudnikov, I.; Dudnik, V.; Gorbenko, A.; et al. (ЦНТУ, 2017)
Проаналізована математична модель прогнозування довговічності робочих органів ґрунтообробних машин з метою вибору ефективного методу їх відновлення. Проанализирована математическая модель прогнозирования долговечности рабочих органов почвообрабатывающих машин с целью выбора эффективного метода их восстановления. The mathematical model of prediction of durability of working bodies of soil-working machines with the purpose of choosing the method of their restoration is analyzed. The process of formation of the geometry of the working surface during its restoration by reinforcing surfacing has been researched and its influence on the increase of durability of the cutting element of the stiffened cultivar leg is estimated. As a result of the conducted research the power characteristic, taking into account the frictional forces acting in the process of working on the arrowhead cultivar paw, is calculated, the density of the distribution of the size of the wear element of the cutting element is calculated.
Повышение долговечности почвообрабатывающих рабочих органов
Improvement of durability of soil working machinery
Keywords: наплавлення; відновлення; сила тертя; технологічний процес; довговічність; ріжучий елемент; математична модель; наплавка; восстановление; сила трения; технологический процесс; долговечность; режущий элемент; математическая модель